Economic evaluations of human milk for very preterm infants: a systematic review - Lu, Anfeng; Huang, Peilu; Guo, Xin; Zhu, Li; Bi, Lei; Xing, Ruirui; Yu, Zhangbin; Tang, Hong; Huang, Guosheng (Frontiers in Pediatrics, 2025)
BackgroundVery preterm infants are highly vulnerable to complications, imposing a significant economic burden on healthcare systems. Human milk has protective effects on these infants, but there is no systematic review on its economic impact.ObjectiveWe conducted a comprehensive review of studies assessing the economic evaluations of human milk for very preterm infants.MethodsOur literature search covered PubMed, Embase, the Cochrane Library, and Web of Science. Two reviewers independently extracted data on economic evaluations and assessed study quality using the Pediatric Quality Appraisal Questionnaire (PQAQ).ResultsFourteen studies of moderate quality, conducted in the United States, Germany, and Canada, met the inclusion criteria. However, the studies analyzed had notable variations and shortcomings. The majority of these studies (n = 11) performed economic evaluations from a healthcare system perspective, utilizing cost-consequence analysis (n = 6) up to the point of neonatal discharge (n = 11). All human milk interventions indicated cost-effective or cost saving results; only a minority included discounting (n = 2).ConclusionThis systematic review suggests that economic evaluation of human milk for very preterm infants is an expanding area of research. Human milk for very preterm infants offers substantial economic advantages during neonatal intensive care unit hospitalization. Standardized and high-quality studies are needed to determine the cost-effectiveness of human milk for very preterm infants in the future.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier (CRD42024539574).